OPTIMALISASI PERAN PESANTREN DALAM PENGEMBANGAN EKONOMI SYARI’AH - Syakur, Ahmad (Fakultas Ekonomi, UIN Maliki Malang, 2009)
On the history of Islam education in Indonesia, the position of pesantren is undoubtful. Before the Islamic school established, for a long time pesantren has given the large contribution for education and building the human resource as quality and quantity. The pesantren with all of the strategic potential, reasonable to be pioneer of Islamic economy. In the other hand Islamic economy need pesantren to grow up. It is caused the pesantren is still being the Islamic education institute that is biggest influencing and being the central of ‘ulama’ education that is legittimed. Actually, the products of Islamic economy is the rich of pesantren, that is observed from fiqh muamalah in the yellow book (kitab kuning). In the head line, the influencing of pesantren in the Islamic economy are two. The first, the influencing of knowledge development; and the second is the influencing to appear the laboratory of sharia economic theory in the real activity. For being maximal the influencing of pesantren in the knowlwdge development in Islamic economy, is required to repair the curriculum, method and management of education. Beside it is required to repair the quality of human resourse, growing interpreneur sense and repairing the management of work.